2018
DOI: 10.1186/s12875-018-0874-7
|View full text |Cite
|
Sign up to set email alerts
|

How older adults self-manage distress – does the internet have a role? A qualitative study

Abstract: BackgroundAnxiety and depression are common in older adults, but often under-recognised by GPs. Rather than perceiving themselves as suffering from anxiety or depression, older adults are more likely to self-identify as experiencing low mood, stress or distress. Older people may also feel responsible for managing their own mood problems. The Internet has the potential to support the self-management of distress through accessing health information or social support.MethodsThis study was approved by Keele Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
1
25
0
2
Order By: Relevance
“…Lastly, we observed that older adults were less likely to use social media or online groups for seeking and sharing health information as well as for social support. Although fewer studies have been published exploring disparities in social media engagement using nationally representative samples [ 29 , 51 , 52 ], additional studies have identified barriers to social media use among older adults including lack of trust, frustration with accessing technology, and preferences towards in-person interactions [ 26 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we observed that older adults were less likely to use social media or online groups for seeking and sharing health information as well as for social support. Although fewer studies have been published exploring disparities in social media engagement using nationally representative samples [ 29 , 51 , 52 ], additional studies have identified barriers to social media use among older adults including lack of trust, frustration with accessing technology, and preferences towards in-person interactions [ 26 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies examining potential explanations for lower rates of eHealth use among particular demographic groups have documented lower rates of trust in health information from internet sources among older adults, racial and ethnic minorities, smokers, and men [ 20 , 23 , 24 , 25 ]. Studies focused on internet use among older adults have observed higher levels of frustration in identifying trustworthy sources of health information and visual inaccessibility of information on internet sites [ 15 , 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults face numerous barriers to technology use (French et al, 2019), including low self-confidence (Czaja et al, 2006; Jung et al, 2010; Siren & Knudsen, 2017), lack of access to affordable devices and broadband (K. Chen & Chan, 2013; Vaportzis et al, 2017), and lack of ongoing (as opposed to one-time) training (Moult et al, 2018; Peek et al, 2016). Social support plays a key role in facilitating older adults’ technology adoption; thus, it may be particularly challenging for older adults with low social support to overcome barriers to technology use (Tsai et al, 2017).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Short video applications can expand the social network of older adults [ 35 ]; the network community can provide social support, promote the self-protection of older adults and provide an opportunity for self-discovery and growth [ 36 ]; and virtual communities can provide a sense of belonging for older adults to assist in the reimplementation of social embeddedness [ 37 ] and provide social participation opportunities for older adults [ 38 ]. The health information provided on the Internet can improve people’s diet and exercise methods [ 18 ] and assist users in pain self-management [ 39 ], thus improving the life and health of users. The role of the Internet in promoting physical health is mainly realized through interaction, information sharing, discussion, and technical support.…”
Section: Introductionmentioning
confidence: 99%